Working Capital Analysis In Increasing Profitability At The Gunungsitoli BNKP PLKT - Giawa, Doniusman; Telaumbanua, Aferiaman; Bate'e, Maria Magdalena; Zai, Kurniawan Sarototonafo (Journal of Management, Economic, and Accounting, 2025)
At PLKT BNKP Gunungsitoli, the researcher found that the lack of efficiency in working capital management—particularly in optimizing the use of current assets such as cash, receivables, inventory, and payables—has resulted in a long cash conversion cycle, thereby limiting the profitability achieved.The purpose of this study is to analyze working capital in improving profitability at PLKT BNKP Gunungsitoli. Data collection techniques include observation and analysis of the company’s financial statements. This research employs a descriptive quantitative method with a ratio analysis approach.The results show that the financial performance of PLKT BNKP Gunungsitoli for the period 2022–2024 experienced a downward trend in cash turnover, receivables turnover, and inventory turnover, as well as fluctuations in payables turnover, all of which remain below industry standards. This indicates low efficiency in working capital management, which can potentially disrupt cash flow and profitability. The ROA also declined from 6.96% to 3.32%, indicating inefficiency in asset utilization. The company needs to improve strategies for managing cash, receivables, inventory, and payables, as well as enhance operational efficiency to strengthen overall financial performance.